A comparative study of the clinical efficiency of chemomechanical caries removal using Carisolv® and Papacarie® - A papain gel - J Kumar; M Nayak; K L Prasad; N Gupta (Indian Journal of Dental Research, 2012)
Objectives: The purpose of this study was to compare the clinical efficiency of chemomechanical caries removal using Carisolv® and Papacarie® - a papain gel. Materials and Methods: The Carisolv® system for caries removal, consisting of a solvent gel and a specially designed hand instrument, was compared to Papacarie - a papain gel. The outcome variables were: time taken for complete caries removal and volume of carious tissue excavated. Forty patients in the age-group of 20-40 years, having Black′s class I dentinal caries with cavity entrance size of ≥3 mm in the molars, were enrolled for the study. The time taken for the complete removal of caries was measured using a stopwatch. Pre- and post-excavation single-step putty/wash elastomeric impression was recorded using addition silicone impression material. Subsequently, casts were poured and measured under a traveling microscope. The total volume of caries excavated was computed using the formula π (d/2)2 h. The difference between the two groups in clinical efficiency and volume excavated was statistically analyzed using the Student′s unpaired ′t′ test. Results: The time for caries removal with Carisolv® and Papacarie® were, respectively, 11.67 ± 3.25 minutes and 10.48 ± 2.96 minutes (P>.05). The mean volume of carious tissue removed with Papacarie® (135.99 ± 66.43 mm 3 ) was higher than that with Carisolv® (126.33 ± 53.56 mm 3 ); however, the difference was not significant. Conclusion: Carisolv® and Papacarie® have similar clinically efficiency as chemomechanical agents for dentinal caries removal.